Ijegbe and Luse Performances, and the Dialects of Collectivized Tragedy and Ideology among the Ilaje - Stephen Ola Ajimisan (Yoruba Studies Review)
This essay explores the genres of Biripo, the Ilaje oral performance or folk-poetry, Ijegbe and Luse vis-à-vis the notion of collectivised tragedy and ideology among the people. Few forays have been undertaken into Biripo, but no known research has been carried out Ijegbe, Luse and collectivised tragedy and ideology among the people. The essay adopts Richard Schechner’s performance theory which sees performance as representation of self and advocates the revolutionary departure from the confinement of theatrical enactments to the theatre. The theory is suitable since the concepts of Ijegbe and Luse are performance-centred. The essay employs oral interviews; secondary materials like textbooks, filmic records of already performed Ijegbe and Luse, journal articles and electronic materials for information garnering.